2021
DOI: 10.1186/s40795-021-00488-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements consumption and its association with socioeconomic factors, obesity and main non-communicable chronic diseases in the north of Iran: the PERSIAN Guilan Cohort Study (PGCS)

Abstract: Background Dietary supplements (DSs) use have become a growing trend worldwide, and it may be affected by demographic and sociocultural factors. Some people use supplements with the thought that they can improve their health, reduce symptoms and prevent disease. The aim of the present study was to define the frequency of DS use and its association with socioeconomic factors among participants with selected main non-communicable chronic diseases (NCDs) (diabetes, cardiovascular disease (CVD), hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
6
11
0
Order By: Relevance
“…In the current study, 79.37% of participants declared no smoking ( p > 0.05 for country and gender). This value agrees with most of the previous works, in which 75.9–88.24% of DS users have been described as ex-smokers and/or non-smokers ( 5 , 22 , 31 , 32 , 37 , 44 , 47 , 63 ). Former studies have indicated a significant, positive association between alcohol absence and DS use ( 24 , 63 , 64 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, 79.37% of participants declared no smoking ( p > 0.05 for country and gender). This value agrees with most of the previous works, in which 75.9–88.24% of DS users have been described as ex-smokers and/or non-smokers ( 5 , 22 , 31 , 32 , 37 , 44 , 47 , 63 ). Former studies have indicated a significant, positive association between alcohol absence and DS use ( 24 , 63 , 64 ).…”
Section: Discussionsupporting
confidence: 93%
“…This value agrees with most of the previous works, in which 75.9–88.24% of DS users have been described as ex-smokers and/or non-smokers ( 5 , 22 , 31 , 32 , 37 , 44 , 47 , 63 ). Former studies have indicated a significant, positive association between alcohol absence and DS use ( 24 , 63 , 64 ). Moreover, the association with different types of alcohol separately has been widely investigated.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with findings from a study in Saudi Arabia which reported that major illness was one of the motivations for DS use among students [ 1 ]. In another study in Northern Iran, participants with a history of obesity, hypertension, cancer and other major illness had greater odds of using DS [ 23 ]. Islam et al (2018) [ 7 ] has also reported that many people in Bangladesh use DS for the treatment of illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the factors contributing to functional food or dietary supplement intake, mainly focusing on gender, age, socioeconomic factors, and health status ( 11 23 ). Although the results are not generalizable ( 11 , 12 ), and are even somewhat contradictory ( 13 , 22 , 23 ), women, older adults, and those with higher levels of education and income were more likely to consume functional foods or dietary supplements ( 14 18 ). Health-conscious people committed to managing their health, such as through physical activity or healthy eating, were more likely to consume functional foods or dietary supplements ( 16 , 18 22 ).…”
Section: Introductionmentioning
confidence: 96%